The Concepts CENTRE and PERIPHERY in the History of Linguistics: From Field Theory to Modern Cognitivism - Skrebtsova, Tatyana (Respectus Philologicus, 2014)
The terms “centre” and “periphery” commonly used nowadays in cognitive studies of language can be traced to earlier linguistic theories. One is field theory advanced by German linguists in the inter-war period. Here, the notions of centre and periphery, along with an array of other spatial images served to visualize the structure of lexical fields. Another tradition in the use of the terms stems from the works of the Prague linguistic circle. Czech scholars claimed that linguistic units vary in their degree of integration into the system. Well -integrated items are associated with the notion of centre while those lacking integration are characterized as peripheral. Cognitive linguistics has offered yet another perspective on the notions concerned. Drawing on Eleanor Rosch’s prototype theory, centre is associated with the category’s best example and periphery with its non-typical members. Thus, terms being the same, their implications differ significantly. It turns out that both field theory and Prague school used them in the context of language-as-an-autonomous-structure view, in accordance with the dominant structuralist paradigm. Cognitive linguistics picked up the psychological approach to the notions of centre and periphery, linking them to subjects’ ratings of category members, and hence to our mental models of the world. These interpretations more often are compatible than non-compatible.